3D genome organization and epigenetic regulation in autoimmune diseases - Qiu, Yueqi; Feng, Delong; Jiang, Wenjuan; Zhang, Tingting; Lu, Qianjin; Zhao, Ming (Frontiers in Immunology, 2023)
Three-dimensional (3D) genomics is an emerging field of research that investigates the relationship between gene regulatory function and the spatial structure of chromatin. Chromatin folding can be studied using chromosome conformation capture (3C) technology and 3C-based derivative sequencing technologies, including 4C, 5C, and Hi-C, which allow scientists to capture of 3D conformations from a single site to the entire genome. A comprehensive analysis of the relationships between various regulatory components and gene function also requires the integration of multi-omics data such as genomics, transcriptomics, and epigenomics. 3D genome folding is involved in immune cell differentiation, activation, and dysfunction and participates in a wide range of diseases, including autoimmune diseases. We describe hierarchical 3D chromatin organization in this review and conclude with characteristics of C-techniques and multi-omics applications of the 3D genome. In addition, we describe the relationship between 3D genome structure and the differentiation and maturation of immune cells, and address how changes in chromosome folding contribute to autoimmune diseases.